Native Centric Ethics Constraining Illegal Migration in Nigeria - Osebor Ikechukwu Monday; Alumona Nicholas Onyemechi; Uchena Chukwuka Obed (Bangladesh Journal of Bioethics)
The fact that young people from Nigeria and Asia make up the largest populations of illegal immigrants overseas is no longer news. The rationale for illegal migration is structural injustice and individual decision-making. Migration has led to increased cultural variety but has also contributed to segregation, racism, and cultural disputes. Stress on the infrastructure, sadness, and anxiety in the host community, and the resurfacing of violence-related post-traumatic disorder attributed to illegal migration. The typical methods for limiting illegal immigration have been nationwide border closures and the repatriation of illegal immigrants. These methods failed to address the issue. Using the method of philosophical analysis, this study maintains that migration has strengthened the economies of many nations and promoted global citizenship and cosmopolitanism, but has led to the deaths of many young Nigerians. The Indigenous Moral Theory of Native-Centric Ethics (togetherness) will be applied to advance and comprehend the causes of illegal immigration as well as potential solutions. Native-centric ethics is the moral of togetherness based on the principles of reciprocity, mutual respect, and working towards the common good. This study concludes that Native-centric ethics should be used by policymakers so that citizens can have faith in their leaders. Of course, this would aid in lowering international unlawful migration.